Oxidative Stress Modulation and ROS-Mediated Toxicity in Cancer: A Review on In Vitro Models for Plant-Derived Compounds. (24th October 2017) - Vallejo, María José; Salazar, Lizeth; Grijalva, Marcelo
Abstract : Medicinal and aromatic plants (MAPs) are known and have been long in use for a variety of health and cosmetics applications. Potential pharmacological usages that take advantage of bioactive plant-derived compounds' antimicrobial, antifungal, anti-inflammatory, and antioxidant properties are being developed and many new ones explored. Some phytochemicals could trigger ROS-mediated cytotoxicity and apoptosis in cancer cells. A lot of effort has been put into investigating novel active constituents for cancer therapeutics. While other plant-derived compounds might enhance antioxidant defenses by either radical scavenging or stimulation of intracellular antioxidant enzymes, the generation of reactive oxygen species (ROS) leading to oxidative stress is one of the strategies that may show effective in damaging cancer cells. The biochemical pathways involved in plant-derived bioactive compounds' properties are complex, and in vitro platforms have been useful for a comprehensive understanding of the mechanism of action of these potential anticancer drugs. The present review aims at compiling the findings of particularly interesting studies that use cancer cell line models for assessment of antioxidant and oxidative stress modulation properties of plant-derived bioactive compounds.